Relasi Alam dan Agama (Sebuah Upaya Penyelarasan antara Budaya Mistis dengan Pelestarian Lingkungan) - Haidi Hajar Widagdo (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
“As khalifa, God assigned to manage nature, but in fact some of them actually, exploiting natural results that ultimately lead to natural disasters all over the places. To refine and guide human intellect and moral management, religion was revealed. Some of religion 'primitive', called animist believes that the universe does have a soul, when the soul is in existence disturbed then they would be angry, and it will harm human beings, this is actually quite similar to what is being taught other religions, especially Islam. Where is the anger of nature that was the result of human action itself.”